Gauge Bosons in the 3-3-1 Model with Three Neutrino Singlets - Long, Hoang Ngoc; Huy, Lam Phu An; Thuy, Tran Thanh; Tran, Ly Thi Tu; Yen, Vu Thi Hoang (Communications in Physics, 2015)
We show that the mass matrix of electrically neutral gauge bosons in the recent proposed model based on \(SU(3)_CSU(3)_LU(1)_X\) group with three neutrino singlets [9] has two exact eigenvalues and corresponding eigenvectors. Hence the neutral non-Hermitian gauge boson \(X^0_μ\) is properly determined.With extra vacuum expectation values of the Higgs fields, there are mixings among charged gauge bosons \(W^±\) and \(Y^±\) as well as amongneutral gauge bosons \(Z, Z’\) and \(X^0\). From the W boson decay width, we get lower bound on scale of the model about few TeVs